KAJIAN INTENSITAS PENERANGAN PADA GEDUNG ELECTRICAL POWER SYSTEM SIMULATOR SEKOLAH TINGGI PENERBANGAN INDONESIA - Khoirul Anam; Soetomo; Adil Alfathan (Politeknik Penerbangan Indonesia Curug, 2017)
Based on the condition nowadays, the lighting systems in electrical power system simulator building has not reached with the standard recommended by Indonesian National Standard (SNI) 03-6575-2001 which the average standard is 500 lux for the laboratory building. To reach the standard, light intensity in electrical power system simulator is necessary to redesign the lighting to fit with the SNI. The theory used in this research is about the theory of lighting, the calculation of lighting levels, etc. In this research, the writer discuss about the design of the lighting in the electrical power system simulator building with recalculate manually using the standard formula in accordance with the SNI, after getting the results of manual calculation, then the calculation is simulated in a Dialux software version 4.12. The output of this Dialux software can display the illumination simulation in the room area and work area. This research is expected to applied immediately so that the intensity of the lighting on the electrical power system simulator building appropriate with the recommended standard lighting by SNI.